REPRESENTASI GENDER DALAM SINEMA HYBRID (ANALISIS SEMIOTIKA LIVE ACTION ANIMATED DALAM FILM INDONESIA PASUTRI GAJE) - Amanda Amalia Faustine Gittawati; Wasvita Sari; Helena Fitri Dewi (Mozaik : Journal of Art and Architecture, 2026)
This study aims to analyze the use of live-action animated techniques in the film Pasutri Gaje as both a representation and a constructor of gender role constructions, as well as a semiotic device that carries layers of social and cultural meaning. The combination of live-action scenes and animation in several sequences produces various signs, such as the use of animation on the male protagonist through a red cape symbolizing heroism and masculinity, which is torn when confronting his father-in-law, who possesses higher authority, signifying the fragility of masculine power. These animated effects not only create visual humor but also open interpretive space regarding gender construction and power relations between men and women within the family. The findings reveal an ambivalent representation of gender. Masculinity in the film is portrayed as heroic, dominant, yet vulnerable, while femininity is associated with emotional and domestic spheres, although it occasionally appears as active and heroic. This dualism emphasizes the negotiation of roles between men and women within the narrative space of household life. Therefore, Pasutri Gaje is not merely presented as an entertaining popular film, but also as a cultural reflection that reveals the persistence of patriarchal values while simultaneously opening possibilities for the reconstruction of gender roles in social life.